2019
DOI: 10.1055/a-1007-1730
|View full text |Cite
|
Sign up to set email alerts
|

Optimal number of endoscopic biopsies for diagnosis of early gastric cancer

Abstract: Background and study aims  No recommendations are available for optimal number of endoscopic biopsies for early gastric cancer (GC), and whether detection of early GC is improved by increasing the number of biopsy is unclear. We therefore evaluated the relationship between number of biopsies and diagnostic accuracy. Materials and methods  We retrospectively evaluated 858 early GCs (623 from endoscopic submucosal dissection and 235 surgical specimens), which we classified as obtained after one, two, or three o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Therefore, for suspected neoplastic gastric lesions that are potentially amenable to endoscopic resection, the number of endoscopic biopsies should be limited. One large retrospective study showed that two endoscopic biopsies yielded a 92.5 % diagnostic accuracy for early gastric neoplasia [68]. Therefore, two biopsies targeted on the most suspicious parts of the lesion should be taken to document the presence of dysplasia or neoplasia.…”
Section: Gastric Cancermentioning
confidence: 99%
“…Therefore, for suspected neoplastic gastric lesions that are potentially amenable to endoscopic resection, the number of endoscopic biopsies should be limited. One large retrospective study showed that two endoscopic biopsies yielded a 92.5 % diagnostic accuracy for early gastric neoplasia [68]. Therefore, two biopsies targeted on the most suspicious parts of the lesion should be taken to document the presence of dysplasia or neoplasia.…”
Section: Gastric Cancermentioning
confidence: 99%
“…Similar filter papers with no tissue bits are also identifiable in the next two biopsies pieces sampled were two or more compared to single tissue piece sampling from endoscopically visible lesions. Increasing the number of tissue pieces by more than two did not show any significantly different diagnostic yield [43,44].…”
Section: 8)mentioning
confidence: 72%
“…Sydney classification has provided an easy concept in understanding the histological parameters by diagrammatic representation of the grades of mucosal changes taking place in the evolution of gastritis of the extent of chronic inflammatory cell infiltration, neutrophil infiltration, and gas-tric glands destruction and loss, extend of replacement fibrosis and goblet cell metaplasia and presence of HP [47]. In order to carry out gradings of the mucosal changes, biopsies are to be taken from different segments of the stomach and every biopsy from a particular segment is to be put into a separately labelled vial so that it can be read and interpreted separately [43,44,46]. While putting the biopsy tissue fragments, it should be made mandatory to orient and mount them on tissue paper for an optimal histological evaluation [45], which may be done with difficulty in cases of small pinch biopsies.…”
Section: 8)mentioning
confidence: 99%
“…To assess not only the primary endpoint but also the key secondary endpoint, 163 gastric cancers were required. Finally, the total sample size was set to 207 cases, considering that approximately 10% would be excluded and the false positive rate of biopsy tissue for the diagnosis of cancer would be 16.2% [25].…”
Section: Discussionmentioning
confidence: 99%